Central versus peripheral cannulation of extracorporeal membrane oxygenation support during double lung transplant for pulmonary hypertension. (8th March 2018) - Glorion, Matthieu; Mercier, Olaf; Mitilian, Delphine; De Lemos, Alexandra; Lamrani, Lilia; Feuillet, Séverine; Pradere, Pauline; Le Pavec, Jérôme; Lehouerou, Daniel; Stephan, François; Savale, Laurent; Fabre, Dominique; et al.
Abstract: OBJECTIVES: Extracorporeal membrane oxygenation (ECMO) has become the standard of cardiopulmonary support during a sequential double lung transplant for pulmonary hypertension. Whether central or peripheral cannulation is the best strategy for these patients remains unknown. Our goal was to determine which is the best strategy by comparing 2 populations of patients. METHODS: We performed a single-centre retrospective study based on an institutional prospective lung transplant database. RESULTS: Between January 2011 and November 2016, 103 patients underwent double lung transplant for pulmonary hypertension. We compared 54 patients who had central ECMO (cECMO group) to 49 patients who had peripheral ECMO (pECMO group). The pECMO group had significantly more bridged patients who received emergency transplants (31% vs 6%, P = 0.001). The incidence of Grade 3 primary graft dysfunction requiring ECMO (14% vs 11%, P = not significant) and of in-hospital mortality (11% vs 14%, P = not significant) was similar between the groups. Groin infections (16% vs 4%, P = 0.031), deep vein thrombosis (27% vs 11%, P = 0.044) and lower limb ischaemia (12% vs 2%, P = 0.031) occurred significantly more often in the pECMO group. The number of chest reopenings for bleeding or infection was similar between the groups. The 3-month, 1-year and 5-year survival rates did not differ between the groups ( P = 0.94). CONCLUSIONS: Central or peripheral ECMO produced similar results during double lung transplant for pulmonary hypertension in terms of in-hospital deaths and long-term survival rates. Central ECMO provided satisfactory results without major bleeding provided the patient was weaned from ECMO at the end of the procedure. Despite the rate of groin and lower limb complications, peripheral cannulation remained the preferred solution to bridge the patient to transplant or for postoperative support.